Improving Teachers Ability In Implementing Learning Outcomes Analysis Through In House Training (IHT) In Madrasah Tsanawiyah Negeri 12 Hulu Sungai Selatan - Birhasani (FKIP Universitas Palangka Raya, 2021)
Research on the implementation of analysis of learning outcomes at MTsN 12 Hulu Sungai Selatan through In House Training (IHT) to improve teachers abilities in learning. This study aims to obtain information about the implementation of in-house training as an effort to improve the ability of MTsN 12 Hulu Sungai Selatan teachers in carrying out analysis of learning outcomes. The method used in this study was the School Action Research which lasted 2 cycles, where the second cycle was an improvement from the first cycle by bringing in observers from the supervisor to observe the implementation of In House Training (IHT). The research subjects were all 24 teachers of MTsN 12 Hulu Sungai Selatan. The data collection techniques used were documentation, tests, and observations. The data analysis technique used is descriptive and percentage. The research results prove that there is an increase in the ability of teachers to carry out the analysis of learning outcomes through In House Training (IHT) from cycle I to cycle II, namely the results of activeness, observation of the implementation of In House Training (IHT) and final assignments with an average of 65.97%. 86.11, The results showed an increase in the ability of teachers to carry out analysis of learning outcomes and In House Training (IHT) was very effective as a learning model.